Knowledge assessment of students’ Kazakh Language acquisition by using Qualimetric methods (Journal of Educational Sciences, 2021)
In the article, the authors present new ideas in the field of qualimetry of modern pedagogy, aimed at identifying the only clear way to provide quality education to the competitive educated generation of Kazakhstan. The article is devoted to the problems of pedagogical qualimetry, which clarifies its scientific significance, and its practical significance is explained by the definition of criteria for assessing the level of proficiency of students in the Kazakh language by classification. The authors describe the application of the concept of qualimetry in the field of pedagogy, the development and formation of the science of pedagogical qualimetry, its relationship with other disciplines, its components. It should be noted that in the system of secondary education there was no real system of assessment certification, which determines the level of knowledge, proficiency, application of the Kazakh language, developed in advanced methods and techniques, and provides qualimetric criteria for the first developed assessment in the pedagogical and philological science of the country. In accordance with international standards for assessing the level of language proficiency, the criteria that must be taken into account in the assessment of reading, listening, speaking and writing skills are classified, and the reason for calling the act of speaking ‘communicative acts’ is justified. The authors provide new analysis in the field of pedagogy by applying international methods of quality certification to assess the quality of education, which leads to effective results in production. In determining the level of language proficiency of a person, the peculiarities of the language studied are taken into account. The authors make a valuable contribution to science in the article, which pays close attention to the nature of the Kazakh language and defines the criteria for assessing the communicative competence of the individual.Keywords: pedagogical qualimetry, communicative competence, skills, assessment, criteria.